The Costs of Price Stability - Downward Nominal Wage Rigidity in Europe - Steinar Holden (Norges Bank, 2002)
In most European countries, the prevailing terms of employment, including the nominal wage, can only be changed by mutual consent. If inflation is so low that nominal wages have to be cut, the workers have strategic advantage in the wage negotiations, which induces higher unemployment in equilibrium. The upshot is a long run tradeoff between inflation and unemployment for low levels of inflation. Specifically, downward nominal wage rigidity, and excess unemployment at zero inflation, are related to three factors: the coverage of collective agreements, the legal framework at contract renewal, and the strictness of the employment protection legislation for non-union workers. Previous versions of the paper have circulated under the title "Monetary policy and nominal rigidities under low inflation". I am grateful John Driscoll, Stein Evju, Daniel Gros, Hans Haller, Kalle Moene, Asbjørn Rødseth, Fredrik Wulfsberg, as well as participants at presentations at CESifo, Harvard University, Virginia Polytechnic and State University, the EEA meeting in Lausanne, University of Essex, Oxford University, FIEF in Stockholm, and the Geilo seminar for useful comments on earlier drafts, to Larry Katz and Greg Mankiw for helpful discussions, and to the NBER for the hospitality when main parts of this paper was written.
hdl:11250/2498654
Keywords: J5; J6; E31; E52; K31; 330; nominal wage rigidity; wage contracts; collective bargaining; monetary policy; inflation; equilibrium unemployment